Clinical investigations for SUS, the Brazilian public health system - Paula, Ana Patrícia de; Giozza, Silvana Pereira; Pereira, Michelle Zanon; Boaventura, Patrícia Souza; Santos, Leonor Maria Pacheco; Sachetti, Camile Giaretta; Tamayo, César Omar Carranza; Kowalski, Clarissa Campos Guaragna; Elias, Flavia Tavares Silva; Serruya, Suzanne Jacob; Guimarães, Reinaldo (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Scientific and technological development is crucial for advancing the Brazilian health system and for promoting quality of life. The way in which the Brazilian Ministry of Health has supported clinical research to provide autonomy, self-sufficiency, competitiveness and innovation for the healthcare industrial production complex, in accordance with the National Policy on Science, Technology and Innovation in Healthcare, was analyzed. DESIGN AND SETTING: Descriptive investigation, based on secondary data, conducted at the Department of Science and Technology, Ministry of Health. METHODS: The Ministry of Health’s research management database, PesquisaSaúde, was analyzed from 2002 to 2009, using the key word “clinical research” in the fields “primary sub-agenda” or “secondary subagenda”. The 368 projects retrieved were sorted into six categories: basic biomedical research, preclinical studies, expanded clinical research, clinical trials, infrastructure support and health technology assessment. From a structured review on “clinical research funding”, results from selected countries are presented and discussed. RESULTS: The amount invested was R 140 million. The largest number of projects supported “basic biomedical research”, while the highest amounts invested were in “clinical trials” and “infrastructure support”. The southeastern region had the greatest proportion of projects and financial resources. In some respects, Brazil is ahead of other BRICS countries (Russia, India, China and South Africa), especially with regard to establishing a National Clinical Research Network. CONCLUSION: The Ministry of Health ensured investments to encourage clinical research in Brazil and contributed towards promoting cohesion between investigators, health policies and the healthcare industrial production complex.